Psychotherapeutic characteristics of schizoid personality - Svynarenko, Yulia (Psychological Counseling and Psychotherapy, 2019)
The article describes the features of psychotherapeutic work with schizoid topic. An understanding of the schizoid psyche in the practical phenomenological direction is considered exclusively under the psychological norm. The main internal conflict of schizoid is described.It shows the strong need for close relationships and the inability to feel comfortably in this proximity. The characteristics of emotional, behavioral, and rational spheres of schizoid individuals are briefly examined. Attention is drawn to features and strategies of psychotherapeutic work with such clients. The first strategy of psychotherapy for a schizoid personality is to create the necessary atmosphere of trust and support, a sense of security in contact with a psychotherapist. The next strategy is to satisfy the demand of a schizoid client to be unconditionally accepted with his unique subjective experience. It is investigated the need for openness and congruence on the part of a therapist. A client in trustful contact with a psychotherapist can recognize his emotional experiences that are unconscious and discarded. Confirmation and reflection of personal feelings in contact with a psychotherapist is sanogenic for a schizoid client. A body-oriented strategy of schizoid-type psychotherapy is considered. The features of the schizoid bodily organization are to block the energy impulses in the muscles. Emotional experiences are disabled due to muscle expression, significant limitation of vital energy in the body. The task of a therapist is to maximally ecologically and fundamentally expand the consciousness of the client to accept personal emotions, needs, experiences and impulses of the body. Client must be ready for a therapist to apply body-oriented techniques. The variants of psychotherapeutic mistakes in work with schizoid dynamics are noted.